STUDENTS’ PERCEPTION IN LEARNING ENGLISH USING COOPERATIVE LEARNING ACTIVITY - Kharisma, Irma; Hidayati, Liza Andhani (IKIP Siliwangi, 2018)
This study aims to know the students’ perceptions about the use of cooperative learning activity in learning English. This study use qualitative research. The sample of this study involved 31 students in class XI social two at SMA Cipta Mandiri in the academic year 2017/2018. In collecting the data the researchers use questionnaire of 20 (twenty) questions that relate to cooperative learning activity. The result of this study shows that most of students agreed if the teacher use cooperative learning activity in the classroom. The students though that through cooperative learning activity, the lesson more interesting and helps them acquire knowledge easily.Keywords: Students’ Perception, Cooperative Learning Actvity